A novel Ba2SrWO6:Mn4+/Dy3+ red phosphors for warm WLED applications - Zhang, Shao-Yu; Tsai, Meng-Hung; Hsu, Tsung-Hsien; Huang, Chi-Yuen; Huang, Cheng-Liang (Materials science & engineering. B, Solid-state materials for advanced technology, 2022)
•The double-perovskite phosphors BSWO: Mn4+ and BSWO: Mn4+, Dy3+ are prepared via the solid-state reaction method.•The optimized concentration of Mn4+ ions is 0.6 mol% along with a CIE chromaticity coordinate of (0.7238, 0.2762) and a color purity of 97.5 %.•The Ba2SrWO6: Mn4+/ Dy3+ phosphors can be tuned in between the CIE chromaticity coordinate from white light (0.3365, 0.3493) to warm white-light (0.4263, 0.3778). A novel non-rare-earth red-emitting phosphor of Ba2SrWO6:Mn4+ with a double-perovskite structure was synthesized via a solid-state reaction method at high temperatures, and the mechanism of structural formation was systematically investigated. Moreover, Dy3+co-dopant ions were exploited to develop a white-light phosphor of Ba2SrWO6:Mn4+/Dy3+. Excitation spectra of Ba2SrWO6:Mn4+ and Ba2SrWO6:Mn4+/Dy3+ were both in a wavelength range of 250–550 nm. Under 325 nm excitation, the Ba2SrWO6:Mn4+ phosphors showed a red emission with a peak at 693 nm because of the 2E → 4A2 transition of Mn4+ ions. The Mn4+ ion concentration in the Ba2SrWO6:Mn4+ phosphors was optimized at 0.6 mol%, and the corresponding CIE (Commission International de I’Edairage) chromaticity coordinate was determined at about (0.7238, 0.2762), locating in the deep-red-light region. Meanwhile, the white-light Ba2SrWO6:Mn4+/Dy3+ phosphors displayed a wide emission band, including a blue emission at 492 nm (attributed to 4F9/2 → 6H15/2), a yellow emission at 582 nm (owing to 4F9/2 → 6H13/2), and the red emission at 693 nm. By varying the Dy3+ ion concentration, the emission color of the co-doped phosphors can be tuned from white light (0.3365, 0.3493) to warm white-light (0.4263, 0.3778), qualifying the phosphorous materials as a potential candidate for white-light- or warm white-light-emitting diode applications.